Współczesne tendencje w obszarze ochrony konsumentów na rynku usług finansowych z uwzględnieniem regulacji instytucji ochrony konsumentów: Rzecznika Finansowego i Prezesa Urzędu Ochrony Konkurencji i Konsumentów - Chashchina, Sofya (Studia Prawa Publicznego, 2021)
The article deals with some issues related to consumer (client) protection on the financial market. Legal regulations constantly change in this area. New regulations are introduced, which makes the subject of consumer protection very topical and important, especially with many accompanying transactions on the financial market. The multiplicity of legal acts and the influence of European legislation, especially EU regulations, can lead to many misunderstandings in terms of terminology. An attempt was made to clarify the concepts of consumer and client on the basis of Polish legislation. According to numerous amendments to the regulation, the entities on the market using financial services should make efforts to conduct a correct assessment of its legal situation and the possibility of using the help of institutions. The range of protected entities differ depending on the legal act that is analyzed. The author draws attention to the ways in which the legislator created a definition of a protected entity and the areas in which it provides legal protection. The analysis also includes legal provisions concerning the competences of institutions performing consumer protection functions: the Financial Ombudsman and the President of the Office of Competition and Consumers, which is a body specializing in individual consumer matters, and a public administration body. Their competences and roles, which overlap in certain areas, have been the subject of lively discussion for a time. This was due to the proposed draft act of December 2020, the provisions of which abolished the institution of the Financial Ombudsman, and transferred his competences to the President of the Office of Competition and Consumer Protection. The paper presents the direction of legal changes in the institutional area of consumer protection of financial services, the ratio of such actions, as well as the outlined European legislator’s vision of adequate consumer protection.